A hadronic scenario for HESS J1818-154 - Castelletti, Gabriela Marta (2013)
Aims: G15.4+0.1 is a faint supernova remnant (SNR) that has recently been associated with the γ-ray source HESS J1818-154. We investigate a hadronic scenario for the production of the γ-ray emission. Methods: Molecular 13 CO (J = 1-0) taken from the Galactic Ring Survey (GRS) and neutral hydrogen (HI) data from the Southern Galactic Plane Survey (SGPS) have been used in combination with new 1420 MHz radio continuum observations carried out with the Giant Metrewave Radio Telescope (GMRT). Results: From the new observations and analysis of archival data we provided for the first time a reliable estimate for the distance to the SNR G15.4+0.1 and discovered molecular clouds located at the same distance. On the basis of HI absorption features, we estimate the distance to G15.4+0.1 in 4.8 ± 1.0 kpc. The 13 CO observations clearly show a molecular cloud about 5´ in size with two bright clumps, labeled A and B, clump A positionally associated with the location of HESS J1818-154 and clump B in coincidence with the brightest northern border of the radio SNR shell. The HI absorption and the 13 CO emission study indicates a possible interaction between the molecular material and the remnant. We estimate the masses and densities of the molecular gas as (1.2 ± 0.5) × 10 3 M⊙ and (1.5 ± 0.4) × 10 3 cm -3 for clump A and (3.0 ± 0.7)× 10 3 M⊙ and (1.1 ± 0.3) × 10 3 cm -3 for clump B. Calculations show that the average density of the molecular clump A is sufficient to produce the detected γ-ray flux, thus favoring a hadronic origin for the high-energy emission.